Polymeric iron chelators for enhancing 5‐aminolevulinic acid‐induced photodynamic therapy. Issue 3 (28th November 2022) - Nomoto, Takahiro; Komoto, Kana; Nagano, Tomoya; Ishii, Takuya; Guo, Haochen; Honda, Yuto; Ogura, Shun‐ichiro; Ishizuka, Masahiro; Nishiyama, Nobuhiro
Abstract: 5‐Aminolevulinic acid (5‐ALA) is an amino acid that can be metabolized into a photosensitizer, protoporphyrin IX (PpIX) selectively in a tumor cell, permitting minimally invasive photodynamic diagnosis/therapy. However, some malignant tumor cells have excess intracellular labile iron and facilitate the conversion of PpIX into heme, which compromises the therapeutic potency of 5‐ALA. Here, we examined the potential of chelation of such unfavorable intratumoral labile iron in photodynamic therapy (PDT) with 5‐ALA hydrochloride, using polymeric iron chelators that we recently developed. The polymeric iron chelator efficiently inactivated the intracellular labile iron in cultured cancer cells and importantly enhanced the accumulation of PpIX, thereby improving the cytotoxicity upon photoirradiation. Even in in vivo study with subcutaneous tumor models, the polymeric iron chelator augmented the intratumoral accumulation of PpIX and the PDT effect. This study suggests that our polymeric iron chelator could be a tool for boosting the effect of 5‐ALA‐induced PDT by modulating tumor microenvironment. Abstract : Polymeric iron chelators efficiently inactivated the intracellular labile iron in cultured cancer cells and importantly enhanced the accumulation of 5‐aminolevulinic acid‐induced protoporphyrin IX, thereby improving the cytotoxicity upon photoirradiation. Even in in vivo study with subcutaneous tumor models, the polymeric iron chelator augmented the intratumoral accumulation of protoporphyrin IX and the effect of photodynamic therapy.